Tualang honey attenuates glutathione depletion in the rat hippocampus following kainic acid administration - Hasim, Hidani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Pasupuleti, Visweswara Rao; Sangu, Muthuraju; Mohd, Asnizam Asari (2022)
Excitotoxicity mediated neurodegeneration by kainic acid (KA) was shown to cause oxidative stress in rats’ brains. Tualang honey (TH), a potential natural medicinal agent, was reported to have many therapeutic properties; however, its protection against neurodegenerative disorders was limited. This study aimed to investigate the protective effects of TH on glutathione levels following KA administration in the rats’ hippocampus. Sprague Dawley male rats (n=24) were randomly divided into four groups which are: (i) control, (ii) KA alone, (iii) TH + KA, and (iv) Topiramate (TPM) + KA, and each group was pre-treated orally with either distilled water, TH (1.0 g/kg) or Topiramate (40 mg/kg), respectively, five times at 12 h intervals. Saline or KA (15 mg/kg body weight) were injected subcutaneously 30 min after the last oral treatment. All animals were sacrificed 24 h after KA injection and their hippocampus was harvested to assay the level of reduced glutathione (GSH), oxidized glutathione (GSSG), and GSH:GSSG ratio by using commercially available ELISA kits. The result showed a significant (p<0.05) decrease in the level of GSH in the KA alone group and was improved by TH pretreatment. Meanwhile, the elevation of GSSG level in the KA-induced group was significantly (p<0.05) reduced by pre-treatments of TH and Topiramate. Remarkably, the pre-treatment of TH was significantly (p<0.05) increases the GSH:GSSG ratio after KA administration. In conclusion, TH showed potential protective effects to prevent oxidative stress-related consequences by attenuating the glutathione system in the rats’ hippocampus after KA administration.